A New Class of Task-Specific Imidazolium Salts and Ionic Liquids and Their Corresponding Transition-Metal Complexes for Immobilization on Electrochemically Active Surfaces - Seidl, Vera; Romero Cordero, Angel Heriberto; Heinemann, Frank Wilhelm; Scheurer, Andreas; Vogel, Carola; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten (Chemistry - A European Journal, 2022)
Adding to the versatile class of ionic liquids, we report the detailed structure and property analysis of a new class of asymmetrically substituted imidazolium salts, offering interesting thermal characteristics, such as liquid crystalline behavior, polymorphism or glass transitions. A scalable general synthetic procedure for N-polyaryl-N’-alkyl-functionalized imidazolium salts with para-substituted linker (L) moieties at the aryl chain, namely [LPhmImHR]+ (L=Br, CN, SMe, CO2Et, OH; m=2, 3; R=C12, PEGn; n=2, 3, 4), was developed. These imidazolium salts were studied by single-crystal X-ray diffraction (SC-XRD), NMR spectroscopy and thermochemical methods (DSC, TGA). Furthermore, these imidazolium salts were used as N-heterocyclic carbene (NHC) ligand precursors for mononuclear, first-row transition metal complexes (MnII, FeII, CoII, NiII, ZnII, CuI, AgI, AuI) and for the dinuclear Ti-supported Fe-NHC complex [(OPy)2Ti(OPh2ImC12)2(FeI2)] (OPy=pyridin-2-ylmethanolate). The complexes were studied concerning their structural and magnetic behavior via multi-nuclear NMR spectroscopy, SC-XRD analyses, variable temperature and field-dependent (VT-VF) SQUID magnetization methods, X-band EPR spectroscopy and, where appropriate, zero-field 57Fe Mössbauer spectroscopy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: carbene ligands; electronic structure; ionic liquids; solid-state structure; thermal properties